Correlation of Carotid Artery Intima-Media Thickness with Age, Body Mass Index and Glomerular Filtration Rate in Chronic Kidney Disease Patients (Medicine Today, 2021)
Introduction: Ultrasound measurements of the intima media thickness (IMT) in the carotid arteries is a strong predictor for cardiovascular events both in the general and diseased population.Materials & Methods: This cross-sectional analytic study was conducted to observe correlation of CIMT with age, body mass index (BMI) and glomerular filtration rate (GFR) in chronic kidney disease (CKD). The study was done in Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, on 80 chronic kidney disease patients, from July 2014 to June 2015. All the biochemical parameters were measured according to the standard laboratory techniques. Body mass index (BMI) was calculated by person’s body weight divided by height. Glomerular filtration rate (GFR) was calculated using the modification of diet in renal disease (MDRD) formula. CIMT measurement was done by duplex study of carotid vessels through high resolution B-mode ultrasound.Results: Mean age of the patients was 36.1±9.5 years. 20 (25%), 26 (32.5%) and 34 (42.5%) patients were in CKD stage 3, 4 and 5 respectively. Age, serum creatinine and GFR showed statistically significant difference among stage 3, 4 and 5 CKD patients (p